2005
DOI: 10.1159/000083268
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Patient Satisfaction of External Dacryocystorhinostomy

Abstract: Purpose: To evaluate patient’s opinion on the long-term success of external dacryocystorhinostomy using the same quantitative parameter pre- and postoperatively. Methods: A postal questionnaire was sent to 139 patients who had undergone external dacryocystorhinostomy. The only parameter for success of the treatment was the improvement of patient’s subjective pre- and postoperative symptoms score. The duration of this follow-up ranged from 1 year up to 5 years postoperatively. Statistical analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Interestingly, only 69% of patients were endoscopic Jones 1 positive, that is, there was less objective success than subjective success. Mansour et al found that, in 139 patients with PANDO who had external DCR, the subjective success rate based on a retrospective symptom score was 89% after 1 year 13. Bakri et al compared quality of life (QOL) outcomes following either external or endonasal laser DCR using the Glasgow Benefit Inventory (GBI) 14.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, only 69% of patients were endoscopic Jones 1 positive, that is, there was less objective success than subjective success. Mansour et al found that, in 139 patients with PANDO who had external DCR, the subjective success rate based on a retrospective symptom score was 89% after 1 year 13. Bakri et al compared quality of life (QOL) outcomes following either external or endonasal laser DCR using the Glasgow Benefit Inventory (GBI) 14.…”
Section: Discussionmentioning
confidence: 99%
“…27 In a study of Fayers et al, the authors suggested that because DCR is performed to improve a patient's quality of life, patient satisfaction is paramount and anatomic patency is secondary. 28 We also think that subjective scoring after DCR is as important as objective evaluation for the assessment of surgical success because symptom relief takes priority over anatomical issues for patients.…”
Section: Current Eye Researchmentioning
confidence: 99%
“…In a study by Mansour et al, long-term patient satisfaction was evaluated after EX-DCR. 27 The patients scored preoperative and postoperative tearing after a long follow-up. The authors concluded that a long postoperative time may negatively affect exact scoring of subjective complaints after surgery.…”
Section: Current Eye Researchmentioning
confidence: 99%
“…As the main complaint that patients present with is epiphora symptomatic improvement is believed to be superior to anatomical patency in determining surgical success. 9,[14][15][16] In a study by Hii et al no significant difference was found between endoscopic-DSR and EX-DSR with regards to surgical outcome or cost, he stated that each case should be managed individually and the choice of surgery be assessed according to patient preference nasal pathology and surgical skill. 17 Our study showed similar anatomical and symptomatic outcomes with previous studies.…”
Section: Discussionmentioning
confidence: 99%